A compact Wi-Fi base station antenna using suspended patch and tapered ground. (2015) - Ding, Hong; Liu, P.F.; Fang, Q.
To expand the bandwidth of Wi-Fi base station antenna and increase the antenna gain, a 4 × 1 suspended microstrip patch antenna array with a tapered ground is proposed. By employing gradually changed and defected ground, the resonant frequency offset caused by the ground plane is reduced, at the same time, the antenna gain is enhanced. Simulated results indicate that the antenna bandwidth with suspended microstrip patch is increased compared with general microstrip antenna. Measured results illustrate that the operating band is from 2.35 GHz to 2.59 GHz with reflection coefficient less than −10 dB (relative bandwidth 8.9%), and the half power beam width (HPBW) of E-plane and H-plane is 60° and 28°, respectively. The maximum gain of this antenna array is 12.6 dB.